Implementation of providing compensation in the form of additional employee income (TPP) for civil servants in the environmental and forestry services of sumedang district - Ipa Hafsiah Yakin (Jurnal Mantik, 2023)
Additional Employee Income is a form of indirect compensation provided to Civil Servants in the form of Additional Employee Income provided by the Regional Government to improve the performance of Civil Servants in accordance with regional financial capabilities. The essence of this research is the implementation of compensation in the form of additional employee income allowances for civil servants at the Environment and Forestry Service of Sumedang Regency. This study used a qualitative research methodology with a descriptive approach. The informants in this study were the Structural Officials at the Environmental and Forestry Service of Sumedang Regency. Data collection techniques through interviews, documentation study and observation. Data analysis techniques are data reduction, data display, data triangulation. The results showed that the additional employee income for civil servants at the Sumedang Regency Environment and Forestry Service refers to the provisions of the prevailing laws and regulations, namely Sumedang Regent Regulation Number 15 of 2019 concerning Amendments to Sumedang Regent Regulation Number 6 of 2019 concerning Additional Employee Income Based on performance, the obstacles in providing additional employee income are the differences in each region in providing additional employee income, inconsistent enforcement of employee discipline, not optimal service quality in the waste management sector and lack of supporting facilities and infrastructure. Suggestions from this study are to conduct socialization related to the provision of additional employee income, rationalization of the proportional amount of additional employee income, and commitment to improving employee work discipline